1999
DOI: 10.1007/s007010050439
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Profiles in Human Gliomas: Quantification by Microbore High Performance Liquid Chromatography and Correlation to Histomorphology and Grading

Abstract: The composition and the content of gangliosides changes during physiological growth and differentiation as well as in neoplastic cell transformation. In order to determine if ganglioside profiles correlate with brain tumour malignancy, the ganglioside distribution was determined in 31 gliomas of astrocytic origin and in non-tumour tissue by a recently developed microbore high performance liquid chromatography (HPLC) method. Glioma malignancy was graded according to the grading system proposed by the World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…GBM tumors are known to either overexpress or synthesize modified forms of GD3, GD2, GM1, GM2, 3Viso-LM1, and 3V6V-isoLD1 (8,10,53,60). Others have reported that gangliosides (mostly GD3 and GM3) are shed into the serum of GBM patients (8,61).…”
Section: Discussionmentioning
confidence: 99%
“…GBM tumors are known to either overexpress or synthesize modified forms of GD3, GD2, GM1, GM2, 3Viso-LM1, and 3V6V-isoLD1 (8,10,53,60). Others have reported that gangliosides (mostly GD3 and GM3) are shed into the serum of GBM patients (8,61).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, neuroectoderm-derived tumors such as neuroblastomas and melanomas and T-cell leukemias express ganglioside GD3 and/or GD2 that have been known as cancerassociated antigens (6,7). Although several reports showed expression of GD3 and GD2 in human gliomas, the roles of these gangliosides have not been demonstrated to date (8,9).…”
mentioning
confidence: 97%
“…Moreover, the results are validated by previous reports on the characterization of lipids from gliomas, each involving initial lipid extraction followed by either HPLC or HPTLC separation. [16,19,20] A follow up biomarker discovery phase will require increasing the sample size to derive and validate classification models. Multiple sampling sites with varying tumor cell density would also contribute to minimizing the effect of a lack of true non-tumor controls inherent to the study of brain diseases.…”
mentioning
confidence: 99%